OVERVIEW OF NEONATAL SEPSIS IN DR. H. MOCH ANSARI SALEH HOSPITAL DURING THE PERIOD FROM JANUARY 2016 - MAY 2017 - REDJEKI, DWI SOGI SRI; MPD, SKG, (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2017)
Background: According to the Demographic and Health Survey(2012), the primary cause of early neonatal death are infections (56%), asphyxia (45%), and congenital abnormalities (11%).Data of neonates who suffer neonatal sepsis obtained at Hospital Dr.H. Moch Ansari Saleh Banjarmasin in the year 2013-2017 is 299 cases Objective: to determine the incidence Overview of Neonatal Sepsis in Dr.H. Moch Ansari Saleh Hospital Banjarmasin, covering the characteristics of mother and baby characteristics. Methods: This research uses descriptive method.Sampling with total sampling is all neonates with sepsis.Data processing is presented through table and calculation of sepsis presentation.This study has secondary data taken from register books, medical records and documented into the research checklist. Results: The mothers of newborns with sepsis aged 20-35 years as many as 46 people (49.46%). Mothers with primiparousparity are asmany as 50 people (53.76%). Mothers with gestational age at term by 62 (59.52%) cases. Mothers who gave birth spontaneously as many as 71 (76.34%). Neonatal sepsis with normal weight were 72 (77.42%). Neonatal sepsis with male gender is the most that is equal to 57 (61.29%). Conclusion: The incidence of neonatal sepsis is more common in women with no risk of primiparous age gestation and spontaneous labor at term. While the characteristics of neonates who have sepsis on normal birth weight and male gender